Fabrication and characterization of pulsed electron beam deposited TiO2 thin films with glancing angle deposition techniques for biosensing application - Dao Quang, Duy; Nguyen, Tri-Nghia; Nguyen, Duy Thien; Nguyen Dinh Hai, Tung; Vu, Thi Huong; Le, Tuan Tu; Vu, Thanh Mai; Le, Van Vu (Vietnam Journal of Science and Technology, 2025)
We demonstrated fabrication and characterization of TiO2 thin films using pulsed electron deposition (PED) with glancing angle deposition (GLAD) techniques. The X-ray diffraction patterns and Raman spectra indicated that the fabricated TiO2 thin films were formed in anatase phases with crystallite sizes of around 20.3 nm. By using the GLAD techniques, the surface morphology and optical properties of TiO2 thin films were well controlled. In particular, the rod-like nanoparticles were probably raised up and the smoothness of the thin films was reduced when incident angles increased from 0º to 70º, which resulted from the self-shadowing mechanism. The absorption coefficient was reduced, the energy band gap increased, and the Raman peaks at 144 cm-1 were vanished with increasing in incident angles in part due to changes in the thin film porosity and the crystallite sizes, which is proportional to the number of self-shadowed induced voiding sites. Furthermore, the non-enzymatic fluorescent glucose sensor using the PED-based TiO2 thin films was demonstrated to explore the application potential of the fabricated materials.